Integrated hormone and transcriptome profiles provide insight into the pericarp differential development mechanism between Mandarin ‘Shatangju’ and ‘Chunhongtangju’ - Huang, Yongjing; Zhu, Congyi; Hu, Yibo; Yan, Sanjiao; Luo, Zhimin; Zou, Yanping; Wu, Wen; Zeng, Jiwu (Frontiers in Plant Science, 2024)
Citrus reticulata cv. 'Chunhongtangju' was mutated from Mandarin 'Shatangju', which has been identified as a new citrus variety. Mandarin 'Chunhongtangju' fruits were late-ripening for about two months than Mandarin 'Shatangju'. To understand the pericarp differential development mechanism in Mandarin 'Shatangju' (CK) and 'Chunhongtangju' (LM), hormones and transcriptome profiles of pericarps were performed in different development stages: Young fruit stage (CK1/LM1), Expansion and Turning color stage (CK2), Expansion stage (LM2), Turning color stage (LM3), and Maturity stage (CK3/LM4). In this study, the development of LM was significantly slower, and the maturity was significantly delayed. At the same stage, most hormones in Mandarin 'Chunhongtangju' pericarps were higher than that in 'Shatangju' such as gibberellin A24, cis (+)-12-oxophytodienoic acid, and L-phenylalanine. The deficiency of hormones in latematuring pericarps was mainly manifested in ABA, 12-OH-JA, MeSAG, and ABA-GE. Differences in transcriptome profiles between the two citrus varieties are primarily observed in energy metabolism, signal transduction such as MAPK signaling pathway and plant hormone signaling, and biosynthesis of secondary metabolites. After analyzing the hormones and transcriptome data, we found that the top genes and hormones, such as Cs_ont_5g020040 (transcription elongation factor, TFIIS), Cs_ont_7g021670 (BAG family molecular chaperone regulator 5, BAG5), Cs_ont_2g025760 (40S ribosomal protein S27, Rps27), 5-deoxystrigol, salicylic acid 2-O-βglucosid, and gibberellin A24, contributed significantly to gene transcription and hormone synthesis.This study suggests that the variances of pericarp development between the two varieties are linked to variations in the transcription levels of genes associated with energy and secondary metabolism, signal transduction-related genes. These findings expand our understanding of the complex transcriptional and hormonal regulatory hierarchy during pericarp development.